The Influence of Perception of Usefulness and Ease of Use on User Decisions of QRIS Digital Payment Application Services in Gorontalo City (Study at Recha Farma Gorontalo Pharmacy) - Pakaya, Sri Afrilliya; Taan, Hapsawati (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the effect of perceived usefulness on the decision of users of the QRIS digital payment application service in Gorontalo City. The sampling technique is non-probability sampling with a total of 96 respondents. Data collection was carried out through observation and the distribution of questionnaires, which were collected using the Cochran formula. Data analysis was performed using simple linear regression analysis, processed with the help of SPSS. The results of this study indicate that perceived usefulness has a positive and significant effect on user decisions. Based on the results of the study, the public considers that QRIS digital payments are easy to learn to use, the system is easy to apply, so it does not require more effort in its use. Meanwhile, the convenience felt by the people of Gorontalo City directly encourages their decision to continue using QRIS in daily payments.